The Impact of Dual Roles of Working Wives on Psychological Well-being and the Influence of Social Support on Family Harmony - Marini; Iffah Royiana; Ummi Masrufah Maulidiyah; Andini Dwi Arumsari; Dzulkifli (P3I UMSurabaya, 2024)
Working wives often face significant challenges in balancing responsibilities at work and at home. This study focuses on the psychological well-being of wives who play dual roles as workers and family caregivers, as well as the impact of the support they receive. Involving 10 participants, the study used in-depth interviews to understand how their well-being affects family harmony. Findings indicate that emotional support from family and colleagues helps them communicate better, create positive interactions, and feel satisfied in family life. This research emphasizes the importance of psychological support programs to help working wives manage the pressures of dual roles.